Análisis y diseño comparativo de un puente de concreto armado de luz variable con otro de sección compuesta - Villanueva Diaz, Rosario (1996)
The constant growth of the population, has always been a latent concern for man and even more so in recent times, since immigration into the towns and regions of greater socio-economic resources, generates a series of requirements, one of which are the routes of land communication and provide bridges that will ensure a proper and permanent service to users. This thesis is not intended to put solution to the huge problem of immigration so deep in its complexity, but always keep the importance and complement constituting the solution of the problem of the design of its streets, which has a huge influence to raise the level of production of peoples, since the male having an efficient and comfortable way with bridges that conform to the requirements of development You can more easily streamline the integration of its inhabitants and the peoples through land transport to ensure its sustainability. L ...